An immutable array of TiO2 nanotubes to pressures over 30 GPa. (10th March 2017) - Zhang, Yanyan; Wang, Qinglin; Zhang, Junkai; Wu, Xiaoxin; Ma, Yanzhang
Abstract: We report the successful formation of an immutable array of α -PbO2 phase TiO2 nanotubes by compression of a TiO2 nanotube array in an anatase phase. During compression to 31.3 GPa, the TiO2 nanotubes started to directly transform from an anatase phase to a baddeleyite phase at 14.5 GPa and completed the transition at 30.1 GPa. Under decompression, the baddeleyite phase transformed to an α -PbO2 phase at 4.6 GPa, which was quenchable to ambient pressure. Notably the tubular array microstructure was retained after the application of ultra high pressure and undergoing a series of phase transformations. Measurements indicated that the nanotubes in the array possessed higher compressibility than in the bulk form. The highly aligned array structure is believed to reinforce the nanotubes themselves, giving exceptional stability. This, as well as the wall thickness, may also account for their different phase transition pathway.